Online learning in PhD educational programs. (Journal of Educational Sciences, 2017)
In the paper the problem of the distance and online learning implementation in the PhD studies is considered. By the analysis of the similar foreign programs, the advances of this learning technology in the PhD studies are highlighted. It’s mobility, flexibility, lower training costs, increase in the number of students and more. However, the implementation of the online learning in the Kazakhstan PhD studies is accompanied by a number of difficulties. The online learning organization scheme which helps toovercome these difficulties is presented.Also the necessary requirements for the creating an official online PhD program which will be able to successfully pass accreditation in the future are presented.It is shown that at the moment only the single factor does not allow to start work on implementing online PhD learning, which is the lack of opportunity to study in the PhD for a fee. The learning system is developed based on modular technology.
Keywords: postgraduate education; PhD; distance learning; online learning; educational program